Mathematics for electronics - Nancy Myers (West Pub. Co., 1993)
Algebra-trigonometry based book bridges the gap between math and technology. Open workbook format includes tear-out pages so that assigned work can be collected. Self-paced examples with solutions and exercises assist students with difficult concepts and allow for self-study. Applications are relevant to students' interest in electronics. Includes chapter on digital mathematics for computer technicians